The Role of Digital Marketing and Relationship Marketing in Purchasing Decisions - Ikut, Camilus Isidorus; Susanto, Aji (Untag Business and Accounting Review, 2025)
This study aims to analyze the influence of digital marketing and relationship marketing on consumer purchasing decisions on the Shopee e-commerce platform. With the development of technology and increasing internet usage, Digital Marketing has become one of the effective marketing strategies to reach consumers more widely. Meanwhile, relationship marketing plays an important role in building customer trust and loyalty. This study uses a quantitative method by collecting data through a questionnaire distributed to 76 respondents, consisting of Management and Accounting students from 2021 to 2024 at the University of 17 Agustus 1945 Semarang. Data analysis was carried out using multiple linear regression analysis through SPSS version 30 software to test the hypothesis in this study. The results of the analysis show that there is a significant positive influence of digital marketing on purchasing decisions, and relationship marketing also has a positive impact on purchasing decisions. This research concludes that digital marketing and relationship marketing have a positive and significant influence on purchasing decisions. Furthermore, the study recommended that Shopee continue to optimize its digital marketing strategy, especially through quality promotions, free shipping programs, and flash sales that have proven to attract consumer interest.